Pengaruh Kemudahan, E-service Quality, Dan Celebrity Endorser Terhadap Keputusan Pembelian Pada E-commerce Shopee (Studi Kasus Pada Mahasiswa Universitas Bahauddin Mudhary Madura: (Studi Kasus Pada Mahasiswa Universitas Bahauddin Mudhary Madura) - jannatul firdaus; Hertin Khalifatun Nisa Arifah (Journal Of Business, Finance, and Economics (JBFE), 2024)
This study intends to investigate, concurrently and in part, how convenience, e-service quality, and celebrity endorsers affect Shopee e-commerce purchase decisions. (case study of students at Bahaudin Mudhary University, Madura). Quantitative research methodology is applied. Up to 100 respondents were sampled using the Slovin formula, which did not reveal the population of this study. Data was collected through a questionnaire filled out by Bahaudin Mudhary Madura University students who had made purchases on Shopee e-commerce. Descriptive statistical analysis, data quality testing, multiple linear regression testing, and hypothesis testing are the types of data analysis that are employed. The e-service quality variable partially did not affect the purchase decision, the celebrity endorser variable partially did not have a significant effect on purchasing decisions, and the convenience variable partially had a significant positive effect on purchasing decisions, according to the t test results. The F test results showed that three variables—convenience, e-service quality, and celebrity endorser—have an impact on Shopee e-commerce purchasing decisions at the same time. In this regard, Shopee must continue to maintain its convenience and further increase the ease of use of its application features so that purchasing decisions on Shopee e-commerce continue to increase.